THE EFFECT OF CORPORATE GOVERNANCE, TENURE AUDIT AND QUALITY OF EARNINGS TOWARDS AUDIT DELAY WITH AUDITOR’S SPECIALIZATION AS THE VARIABLE OF MODERATION - Reni Yendrawati; Anggi Prayuda Panggabean (Asian Journal of Innovation and Entrepreneurship, 2016)
This study was aimed to find out the effect of corporate governance, tenure audit, and quality of earning towards audit delay (audit report lag) with auditor’s specialization as the variable of moderation (empirical studies on manufacturing companies listed in Indonesian Stock Exchange in 2011-2013). Corporate governance authorized with the managerial ownership, independent board, institutional ownership, tenure audit and quality of earning became independent variables. Audit delay (audit report lag) became the dependent variable. The total of samples tested by 67 companies was selected by purposive sampling method. The data used is secondary data with the media in the form of financial reports of manufacturing companies. This study analyzed the company's audited financial reports by employing an analysis technique using descriptive and statistical analysis. The finding of this study indicated that the tenure audit moderated by auditor’s specialization provides audit delay which is shorter than the non-specialist auditors, while managerial ownership, independent board, institutional ownership and quality of earning is not proven to be moderated by the auditor’s specialization towards audit delay.